What is Said and What is Understood? The Readability and Language of Child Protection Medical Reports. (20th February 2019) - Cutland, Michelle; Sims, Jo; Pye, Matthew; Rourke, Catherine; McMullan, Kirsty; Linden, Anna; Jones, Steve
Abstract : Key Practitioner Messages Child protection medical reports provide the voice and opinion of a paediatrician, and must be readable by all. Child protection medical reports should include a professional opinion even if the opinion is one of being unsure. Simple measures can improve the readability of reports. A number of descriptive words are used in the opinions of reports. Standardisation of these could be encouraged to reduce misinterpretation. 'Child protection medical reports provide the voice and opinion of a paediatrician, and must be readable by all'